ANALYSIS OF TSUNAMI EVACUATION ROUTE PLANNING IN KULON PROGO REGENCY - Bernadeta Aurora Edwina Kumala Jati; Muhammad Falakh Al Akbar; Tri Wahyuni; Ernani Uswatun Khasanah; Amelia Rizki Gita Paramanandi; Hubertus Ery Cantas Pratama Sutiono; Dwiana Putri Setyaningsih; Wirastuti Widyatmanti; Totok Wahyu Wibowo (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2023)
Situated on the southern coast of Java Island, Kulon Progo Regency is prone to tsunami hazards since it directly faces the subduction zone of the Eurasian Plate and the Indo-Australian Plate. The road condition on the coast of Kulon Progo Regency, which extends from east to west, can be an obstacle in the evacuation process if there is no proper evacuation route planning. Total population in the study area reached 149,574 people. Therefore, it is essential to plan an evacuation route in the coastal area of Kulon Progo Regency. This study proposes the tsunami evacuation route and evaluates it with field conditions on the coast of Kulon Progo Regency. The evacuation route was built using Multi-Criteria Based Least Cost Path Analysis, which uses road network, land use, and slope data as parameters. The least cost path analysis for determining the evacuation route was carried out in 2 scenarios, namely for vehicles and pedestrians. The results of the least cost path analysis of the vehicle scenario are considered less suitable because the results are more through land use and away from the road network. The pedestrian evacuation scenario is more in line with reality because it produces a path adjacent to the road network so that it can be passed either by vehicle or pedestrian.